Formation and mobilization of methylmercury across natural and experimental sulfur deposition gradients - Åkerblom, Staffan (Swedish University of Agricultural Sciences, 2020)
Examine methylation of mercury in a west-east gradient in southern Sweden to cover a natural sulfur-deposition gradient. Peat samples were taken at a depth of 5-30 cm below the surface between May 15 and June 12 in 2003.

Peat soil and porewater samples were collected during the summer of 2003 to describe methylationprocesses in peatlands across a natural sulfate deposition gradient.

Undersöka metylering av kvicksilver i en väst-östlig gradient i syd-Sverige som täcker en naturlig svaveldepositionsgradient. Torvprover är tagna på ett djup av 5-30 cm mellan 15 maj och 12 juni, 2003

Torvprover och porvatten har samlats in under försommaren 2003 för att beskriva metyleringsprocesser i torvmark i en naturlig gradient av sulfatdeposition.
Metylering av kvicksilver i naturliga och experimentella svaveldepositionsgradienter
Keywords: Geology; Geologi; Mercury; Kvicksilver; Soil; Mark; mercury methylation; kvicksilver metylering; Natural Sciences; Naturvetenskap; Earth and Related Environmental Sciences; Geovetenskap och relaterad miljövetenskap; Biological Sciences; Biologi; Geoscientific Information; Geovetenskap; Environment; Miljö